Distribución espacial de la Preñadilla (astroblepus cyclopus) en la cuenca alta del rio Pumacunchi, provincia de Cotopaxi. - Villacís Orozco, Diego Andrés (2019)
The research work began with a visit to the Guaytacama Parish in order to proceed with the recognition of the space to be analyzed, which allowed the collection of information to analyze the water of the Pumacunchi River. This was done prior to a talk with the inhabitants of the parish who gave reports about the existence of the species in the community near the riverbanks. The in-situ visit served to spatially delimit the micro-basin, after which we went to verify the habitat where the existence of Astroblepus Cyclopus was presumed. The samples were collected in bottles that were duly sterilized and immediately transported in a cooler so as not to alter their quality indexes. Subsequently, using the CSV format (delimited by commas), the spatial distribution and delimitation of the Pumacunchi River basin was established, indicating the points found where the presence of the species was observed. A limited number of the pregnant specimens could be located in a natural formation, a sort of pool-like annex, thus finding a total of 20 specimens in 3 of the 17 points that were taken with the help of GPS. At the same time, water analysis was carried out to determine pH, cyanuric acid, chloride, turbidity and dissolved oxygen based on Book VI of Annex 1 of the TULSMA standards. This also yielded results such as the presence of contaminating elements in abundance, bovine animals that freely expel their feces directly into the river. Based on the Shapefiles provided by the National Information System, a segregation of elements compatible with the subject of the investigation was made, with which it was possible to determine the vegetation coverage, soil erosion and slope of Guaytacama Parish.